Образование синергетического эффекта в туризме как результат функционирования логистических сервисных систем - Скоробогатова, Т. (Вісник економічної науки України, 2012)
Рассмотрена специфика общесистемных свойств и характеристик применительно к логистическим сервисным системам, функционирующим в сфере туризма. Показано образование синергетического эффекта производства и потребления в логистических сервисных системах, базирующихся на различных объединениях. Развиты положения концепции городов-связей. Розглянута специфіка загальносистемних властивостей і характеристик стосовно логістичних сервісних систем, що функціонують у сфері туризму. Показано утворення синергетичного ефекту виробництва і вжитку в логістичних сервісних системах, що базуються на різних об'єднаннях. Розвинені положення концепції міст-зв'язків. Experience of reorganization of personnel service in more volume, with expanded functions of human resource management on an example of private joint stock company «Tekhnika» is considered. Classifications of the purposes, system of indicators which are offered at carrying out diagnostics of labor productivity are given. The scale of awarding of operation personnel, heads and leading experts of the company which considers specifics of each group of workers is developed. Research of management process by the personnel, estimation of quality of use of human resources promotes identification of possible reserves of increase of labor productivity.